Odpowiedź:
[tex]a) 3x+\frac{6}{2}x-6*x+\frac{3}{4}x+8=3x+3x-6x+\frac{3}{4}x+8=6x-6x+\frac{3}{4}x+8=\frac{3}{4}x+8\\ \\ b)\frac{2}{x}+5 : \frac{4}{6}x+30=\frac{2}{x} +5*\frac{6}{4x}+30=\frac{2}{x}+\frac{30}{4x} +30=\frac{8}{4x}+\frac{30}{4x}+30=\frac{38}{4x}+30\\ \\ c) 4x^2-\frac{9}{x^2} +5x+6:2x^2-7x+\frac{6}{x^2} -4= 4x^2-\frac{9}{x^2}-2x+\frac{3}{x^2}+\frac{6}{x^2}-4=(znajdujemy wspolny mianownik)=\frac{4x^4-9-2x^3+3+6-4x^2}{x^2}=\frac{4x^4-2x^3-4x^2}{x^2}=\frac{x^2(4x^2-2x-4)}{x^2}=4x^2-2x-4[/tex]
Szczegółowe wyjaśnienie: